Filterable PM2.5, Metallic Elements, and Organic Carbon Emissions from the Exhausts of Diesel Vehicles - Yuan-Chung Lin; Ya-Ching Li; Kassian T. T. Amesho; Feng-Chih Chou; Pei-Cheng Cheng (Aerosol and Air Quality Research)
Abstract Urban air pollution in the form of fine particulate matter (PM2.5) poses a substantial health threat to humans via inhalation. To assess the risks from this pollutant, we characterized and quantified the PM2.5 exhausted by 15 diesel vehicles ranging from 28,306 to 883,374 km (an average of 525,854 km) in total mileage and varying in manufacturer and model year (1988–2005). We applied inductively coupled plasma optical emission spectroscopy (ICP-OES) to analyze the metallic element constituents, among which Ca composed the largest fraction, followed by Zn, Al, K, Fe, Mg, and Cr. Measuring the carbonaceous content, we found that the total carbon (TC), the organic carbon (OC), and the elemental carbon (EC) accounted for 3461 µg m−3, 1410 µg m−3, and 2051 µg m−3 of the PM2.5 concentration, respectively. Of the metallic elements, Ca exhibited the highest emission factor (EF), between 45.3 and 259 µg L-fuel−1 (with an average of 132 µg L-fuel−1), whereas Zn and Cr displayed the lowest ones, averaging 13.1 µg L-fuel−1 and 1.91 µg L-fuel−1, respectively. We also investigated the relationship between the concentrations and the EFs of the metallic elements in the exhaust, and the ambient PM2.5 composition. These results help illustrate the contribution of PM2.5 emitted by diesel vehicles to metallic element concentrations in the natural environment and the consequent risks.